Sosialisasi dan Pelatihan Membangun Wirausaha Muda pada Sekolah Menengah Kejuruan - Ahmad, Deni Nasir; Setyowati, Luluk; Andayanti, Westri (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The aim of community service activities by the service team is 1. to build confidence and motivation of young people to take a role in the economy, namely in the field of entrepreneurship. 2. Making partners, especially students from our partner, namely Al-Wahyu Vocational School, in accordance with their vision, namely making them intelligent, skilled, professional and entrepreneurial. The methods used in this activity are: a. Direct observation means that the service member comes directly to the service location to collect data. b. Carrying out community service activities by conducting outreach and training to community service partners. c. Carrying out evaluations and sharing together to produce final results of activities. The results of the activity are that students are motivated to start a business at a young age and are trained in selling products with friendly marketing. Conclusion of the activity: Participants were enthusiastic in preparing themselves for self-employment and entrepreneurship at a young age, starting from financial planning to preparing for business creation. b. The training participants provided a lot of input to the service team so that service activities could be continued and other training programs could be held.